Insight into the role of hydrogen addition to improve combustion and emission characteristics of marine diesel-piloted premixed ammonia engine - He Yang; Lin Lyu; Yongzhong Huang; Liang Yang; Junjie Liang; Yue Chen; Neng Zhu; Ying Sun (Fuel, 2026)

A novel efficient numerical method for 3D bi-anisotropic photonic crystal simulation - Ke Gui; Tiexiang Li; Wen-Wei Lin; Xing-Long Lyu (Computer Physics Communications, 2026)

Defect-engineered Cu-TCPP/ZIF-L nanosheet-modified PVDF membrane with enhanced water purification and dye removal performance - Yiming Zhao; Jingyuan Zhang; Junmei Liu; Jiatong Han; Dan Xu; Jing Wang; Fengzhi Lyu; Lin Qin; Donghui Xu; Ge Chen; Guangyang Liu (Chemical Engineering Journal, 2026)

Production of phloretin by multi-module carbon flux rewiring in Saccharomyces cerevisiae - Yi Wu; Jiali Gu; Hongye Li; Lin Wang; Qixiao Zhai; Wei Zhao; Rujin Yang; Xiaomei Lyu (Bioresource Technology, 2026)

A high-throughput strategy for screening umami peptides from Chouguiyu based on peptidomics and machine learning-assisted molecular simulation - Sitong Lyu; Shichao Xuan; Fan Yang; Honglin Yu; Di Meng; Jianqing Zhou; Cristabelle De Souza; Zhe Zhang; Tongjie Liu; Huaxi Yi; Qingjuan Tang; Lanwei Zhang; et al. (Food Research International, 2026)

Mycorrhizal associations influence the origin and stability of topsoil organic carbon fractions: implications for subtropical forest restoration - Yongmeng Jiang; Maokui Lyu; Haohao Su; Yuming Lu; Cui Deng; Jueling Liu; Man Wang; Weisheng Lin; Jinsheng Xie (Forest Ecology and Management, 2026)

Climatology of extreme convective systems in China from joint TRMM and GPM observations - Jiahao Lin; Xiaoteng Huang; Zihao Zhang; Xingyi Lin; Yuhang Hu; Yanbo Wang; Xiaoqun Hu; Fanchao Lyu; Xueke Wu (Atmospheric Research, 2026)

Recent progress on hydrogen production via catalytic Auto-thermal methane Reforming: A focus on catalysts and operational parameters - Jun Wan; Peng Liu; Feiyi Zhou; Huajie Lyu; Teng Hu; Keyu Cheng; Yihong Song; Jiabiao Zou; Xiao Zhang; Saisai Lin; Chenghang Zheng; Xiang Gao (Fuel, 2026)

Wendan decoction ameliorates chronic obstructive pulmonary disease via regulating pulmonary microbiota homeostasis and inhibiting NOD-like receptor pyrin domain-containing 3-Caspase1 pathway: Integrating chemical profiling, efficacy validation and molecular mechanism elucidation - Song Lin; Qi Yu; Guoan Zhao; Xuanyu Fu; Yuyang Chen; Shutong Chen; Ying Lyu; Weiwei Jia; Yuran Sun; Wenbao Wang; Tianyang Wang; Yan Lin (Food Bioscience, 2026)

Interfacial and emulsifying properties of low-denatured soy protein prepared by self-coacervation - Shumin Zhang; Jiyang Cai; Zhuojia Lin; Chang Yang; Zhihong Lyu; Menghui Wang; Wentao Qian; Zhili Wan; Hongliang Li; Xiaoquan Yang (Food Hydrocolloids, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

ADAMTS7 selective inhibitor BAY-9835 alleviates acute myocardial infarction by suppressing the NF-κB-mediated pyroptosis - Yunzhi Ling; Yang Lyu; Hanchuan Chen; Biting Lin; Gengyu Zhou; Simiao Chen; Tingting Weng; Ziqing Ruan; Yuanfan Zhu; Zhaoju Zhu; Yansong Guo; Kaiyang Lin (Toxicology and Applied Pharmacology, 2026)

Failure risk assessment and dominant cause analysis of an integrated point-absorber wave energy converter in a semi-submersible wind–wave hybrid system - Zhiyang Zhang; Shuaidi Lyu; Serhii Morhun; Weixing Liu; Lin Cui; Haitao Wu (Ocean Engineering, 2026)

PigTracker: Sequential-vertices-based tracking framework for intelligent pig farming - Weijia Lin; Xinyuan He; Ziwei Li; Zhixiong Zeng; Yanhua Liu; Enli Lyu; Junduan Huang (Computers and Electronics in Agriculture, 2026)

Biosensor-driven evolution of oxidoreductive pathway for efficient tagatose production by Saccharomyces cerevisiae - Chenyu Xu; Haitao Hu; Lin Wang; Ruru Sun; Qixiao Zhai; Wei Zhao; Ruijin Yang; Xiaomei Lyu (Food Bioscience, 2026)

PigInstance: An efficient Pig Instance segmentation framework for intelligent pig farming - Weijia Lin; Xinyuan He; Ziwei Li; Enli Lyu; Yanhua Liu; Zhixiong Zeng; Junduan Huang (Computers and Electronics in Agriculture, 2026)

Feedback-driven adaptive variable grouping for decomposition-based large-scale multiobjective optimization - Qi Liu; Rui Lin; Li Lyu (Swarm and Evolutionary Computation, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Mycorrhizal-association type mediates soil priming effect and its response to nitrogen addition in subtropical plantations - Wei Zhang; Xiao-Hong Wang; Liming Yin; Maokui Lyu; Lin-Qiao Jia; Li-Li Wang; Ai-Ping Liu; Xiao-Die Hu; Xiaodong Yao; Guang-Shui Chen (Pedobiologia, 2026)

Environmental stress drives microbial regime shifts and functional reorganization in a large deep reservoir - Xucong Lyu; Jing Dong; Xiaofei Gao; Jingxiao Zhang; Penghui Zhu; Haiyan Chen; Huatao Yuan; Yunni Gao; Xuejun Li; Senjie Lin (Environmental Research, 2026)

Influence of tropical cyclones on organic aerosols in a coastal city of South China - Hongxing Jiang; Yuanhang Deng; Hai Guo; Yunxi Huo; Dawen Yao; Haoxian Lu; Changliu Wu; Meiyi Fan; Xiaopu Lyu; Fengwen Wang; Yan-Lin Zhang; Fan Zhang; et al. (Atmospheric Research, 2026)

Precipitation reduction mitigates the negative impact of nitrogen deposition on soil nitrogen fixation in subtropical Chinese fir plantations - Fengyi Han; Yongxin Lin; Maokui Lyu; Hang-Wei Hu; Xiangyin Ni; Qiufang Zhang; Jinsheng Xie; Ji-Zheng He; Peter M. Homyak (Science China Life Sciences, 2026)

Quantifying Predictive Uncertainty in Hemodialysis: A Dynamic Ensemble Selection Framework Based on Interval Quality - Hsuan-Ming Lin; JrJung Lyu (Journal of Medical and Biological Engineering, 2026)
Purpose In high-stakes medical domains like hemodialysis, models must provide reliable prediction intervals (PIs) that quantify uncertainty, not just point predictions. Standard ensembles are often static. This study proposes and evaluates a novel Uncertainty-Aware Dynamic Weighting Ensemble (UADWE) framework to improve the reliability of blood pressure PIs during hemodialysis. Methods The framework dynamically assigns weights to a pool of base models based on their localized performance. Competence is measured by each model’s historical ability to generate high-quality PIs on similar instances. This adaptive mechanism was validated on a real-world clinical dataset from a hemodialysis center using a rigorous repeated grouped k-fold cross-validation protocol to ensure robust evaluation. Results The proposed UADWE framework achieved a statistically significant improvement in prediction interval quality (p-value <0.001), obtaining an Interval Score of 50.18 with a small but consistent advantage over Simple Averaging (50.50) and a substantially larger margin over Stacking ensembles (scores > 59). Concurrently, the framework achieved an overall Prediction Interval Coverage Probability of 90%, matching the nominal target; stratified analysis revealed conservative over-coverage in the data-dense central blood-pressure range and progressive under-coverage in the low-density tails (<100 and >180 mmHg) for all evaluated models including UADWE. Point prediction accuracy remained competitive with the best individual learners (RMSE $$≈$$ 11.7). Conclusion This work introduces a novel dynamic ensemble framework with improved prediction interval quality. We demonstrate that the synergy between a dynamic, uncertainty-aware strategy and a well-curated, diverse model pool enhances reliable interval estimation, though external validation is needed before clinical translation.

Extraction of Stratospheric Aerosol Extinction Profiles from Limb-Scattering Signals Measured by the BLS onboard the Tiangong-2 Space Laboratory - Song Liu; Peng Zhang; Lin Chen; Na Xu; Minzheng Duan; Daren Lyu (Advances in Atmospheric Sciences, 2026)

Functional complementarity of abundant and rare taxa mediates soil carbon sequestration during subtropical forest restoration - Yuming Lu; Maokui Lyu; Yongmeng Jiang; Cui Deng; Jueling Liu; Man Wang; Weisheng Lin; Jinsheng Xie (Journal of Environmental Management, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Wine processing induced structural modification of Polygonati Rhizoma polysaccharide and their enhancement of Tc1 cell immunomodulatory activity via microbiota-mediated butyrate metabolism - Fenghe Yang; Chun Wang; Zhiqian Song; Shitao Peng; Ziqi Tian; Wenjie Lu; Tao Lin; Qiao He; Aiping Lyu; Zhangchi Ning (Carbohydrate Polymers, 2026)

Global inland waters trophic status from space observation: scientific advances and future challenges - Lili Lyu; Pierre-Andre Jacinthe; Nan Lin; Dongmei Lyu; Ge Liu; Sijia Li; Chong Fang; Hui Tao; Hao Yu; Zuchuan Li; Kaishan Song (Water Research, 2026)

Anthropogenic acids alter carbon sinks in a temperate karst catchment: Insights from multi-isotopic tracers - Jie Zhang; Lin Zhang; Shuangmei Tong; Jiejie Lyu; Jia Yuan; Menggui Jin (Journal of Hydrology, 2026)

Climate change intensifies carbon emissions from the Earth's Third Pole: Projected trajectories of soil and ecosystem respiration - Tongqing Shen; Zhongbo Yu; Qin Ju; Junliang Jin; Guoqing Wang; Yanli Liu; Chunming Hu; Shixuan Lyu; Hui Lin; Xinrong Si; Feng Yan (Global and Planetary Change, 2026)

Digital transformation of Jiangxiangxing Baijiu production: integrating flavor compound analysis, machine learning recognition, and genetic algorithm blending of multi-rounds - Xiaotong Lyu; Qi Jiang; Kemin Linghu; Yifei Zhou; Mengqian Yu; Chunhui Wei; Liangcai Lin; Qi Zhou; Zhengshu Zhou; Cuiying Zhang (Food Research International, 2026)

Integrated multi-omics and machine learning reveal aroma profiles and brand fingerprints in various fermented mandarin fish - Jian Shi; Shichao Xuan; Sitong Lyu; Fengzhi Qiao; Qingjuan Tang; Naiyong Xiao; Mingyu Yin; Wenzheng Shi; Lanwei Zhang; Jianan Sun; Yongxiang Wu; Kai Lin (Food Bioscience, 2026)

Integrated plastic film and straw mulching enhances potato tuber yield in mountainous regions by optimizing rhizospheric metabolites and root–microbe interactions - Kang Du; Xinyue Yang; Zhenpeng Deng; Xi Lin; Mengyuan Hu; Rui Jiang; Guolian Zheng; Xiaoping Yi; Xun Liu; Changwen Lyu; Jichun Wang (Field Crops Research, 2026)

Parylene-C templated synthesis of hierarchical bismuth nanoflowers for reversible chloride-ion storage - Sanjay Ballur Prasanna; Jian-Lin Lyu; Yu-Lin Lee; Ren-Jei Chung; Hong-ming Ku; Po-Chun Chen (Chemical Engineering Journal, 2026)

Infra-slow body-surface potentials show a group-level association with thyroid cancer - Bohan Deng; Ruili Zhang; Yuxuan Liu; Jinglao Lin; Shicong Gui; Xihao Wei; Yin Cheng; Li Zheng; Shaohua Hu; Pingping Lyu; Yubo Li; Huafen Wang (Journal of Zhejiang University-SCIENCE B, 2026)

Potential mechanisms of phosphorus removal in bioelectrochemical systems: The synergy between electrochemical precipitation and the effects of microorganisms - Xinhui Lin; Xiaoxia Huang; Xiaowen Li; Ping Lyu; Yuchen Liu; Xianqiao Tao; Yanhong Jiang (Journal of Water Process Engineering, 2026)

An overview of GNSS for tsunami early warning: From lithosphere to ionosphere - Kejie Chen; Haishan Chai; Jiafeng Li; Guoguang Wei; Mingzhe Lyu; Wenfeng Cui; Chuang Shi; Linlin Li; Peitao Wang; Wei Lu; Jian Lin (Science China Earth Sciences, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Long-term operational strategy of microalgal-bacterial granular sludge towards strengthened sulfadiazine antimicrobial resistance control - Shupeng Lin; Minmin Pan; Yanfang Ma; Zhihao Chen; Tao Lyu; Renjie Dong; Roger Ruan; Shan Liu (Journal of Hazardous Materials, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Impact of infant feeding conditions on the survival and post-digestive regrowth of commercial probiotics in an in vitro gastrointestinal model - Juan Wang; Ni Wang; He Lyu; Peng Wu; Jia Lin; Xiao Dong Chen (International Dairy Journal, 2026)

Exogenous phospholipid intermediates mediate membrane lipid composition remodeling to enhance spray-drying survival of Lactobacillus bulgaricus - Fengzhi Qiao; Meijun Liu; Wenhao Ding; Sitong Lyu; Zhe Zhang; Tongjie Liu; Huaxi Yi; Lanwei Zhang; Kai Lin (Food Bioscience, 2026)

Microalgae-mediated shaping of bacterial communities enhances antibiotic removal and antibiotic resistance control - Shupeng Lin; Minmin Pan; Yanfang Ma; Zhihao Chen; Tao Lyu; Renjie Dong; Roger Ruan; Shan Liu (Bioresource Technology, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Microbial processing of organic matter in cold seep sediments revealed by amino compound distributions and degradation indices - Yang Wu; Lina Lyu; Meiqing Lin; Shengtao Ma; Cheng Yang; Rong Wu; Kaiqin Huang; Xi Xiao; Yifei Dong; Binbin Guo; Danyi Su; Jing Zhao; et al. (Marine Pollution Bulletin, 2026)

Microbial degradation of short-chain chlorinated paraffins in marine environment: bacterial community responses, functional genes, transformation products, and metabolic mechanisms - Lina Lyu; Li Zhang; Cheng Yang; Yanqun Li; Hao Yin; Lin Wang; Zhimao Mai; Si Zhang (Water Research, 2026)

Characteristics of Extratropical Cyclones and Associated Precipitation Across the Huang‐Huai River Basin, East China - Zhiqiang Lin; Long Jiang; Xiuping Yao; Linyi Lyu; Ke Li; Caiyun Feng (International Journal of Climatology, 2026)
The Huang‐Huai River Basin (HHRB) in East China is highly susceptible to frequent floods and droughts, making it one of the most disaster‐prone regions in China. Extratropical cyclones (ETCs) are the primary weather systems generating precipitation over the HHRB. This study investigates the spatiotemporal characteristics and precipitation patterns of ETCs affecting the HHRB, based on a long‐term dataset (1979–2022) derived from ERA5 reanalysis. On average, 33.2 ETCs traverse the HHRB annually, exhibiting a statistically insignificant increasing trend over the study period. Most ETC activity occurs during summer months and nighttime hours. ETCs contribute to approximately 60% of the HHRB's total precipitation, with their contribution increasing for more intense precipitation events. Based on source regions and tracks, the ETCs are classified into five distinct types: locally generated systems and those originating from northwestern, northeastern, southwestern, and southern China. Locally generated ETCs produce the largest total precipitation, whereas those originating from southwestern China trigger the most intense rainfall events. ETC‐induced precipitation plays a crucial role in driving summer floods and droughts over the HHRB. Consequently, a deeper understanding of the characteristics, formation mechanisms, and precipitation‐generating processes of these systems is essential for effective disaster prevention and mitigation strategies.

Stress Behaviors of Cartilage with Defect and After Repair in Total Knee Under Compression Loading - Xianglong Lin; Shilei Wang; Bolun Liu; Lilan Gao; Linwei Lyu; Chunqiu Zhang (Journal of Medical and Biological Engineering, 2025)

Hunting, gathering, planting, and animal rearing: Utilization of animal and plant resources at the Wutaishan site (5800–5300 a BP), Songhua River Basin, Northeast China - Lin Ban; Wuyu Zhou; Xiaohong Lyu; Yixue Wang; Yonggang Sun; Chunxue Wang (Journal of Geographical Sciences, 2025)

Vertical variation of E. coli O157:H7 survival in a black soil column under freeze-thaw cycles conditions - Jiawen Lu; Jinhua Ma; Guangze Lyu; Xinran Lin; Jiayang Hu; A. Mark Ibekwe; Jincai Ma (Applied Soil Ecology, 2025)

Generative Model Enhanced X-ray Computed Tomography Imaging for Pharmaceutical Powder Microstructure Reconstruction and Evaluation - Leqi Lin; Xingyu Zhou; Yuetong Ding; Guangyao Lyu; Xizhong Chen (AAPS PharmSciTech, 2025)

Environmentally friendly, lightweight, and recyclable nanocomposite foams for sustainable electromagnetic interference shielding via integrating a dynamically crosslinked biobased polyamide system with supercritical carbon dioxide foaming - Chia-Hsing Lin; Chia-Wei Lee; Lyu-Ying Wang; Rui-Hao Li; Yi-Huan Lee (Chemical Engineering Journal, 2025)

Rapid and efficient removal of aqueous perfluorooctane sulfonate at environmentally relevant concentrations using photoregenerable modified biochar - Dongjiao Lin; Honghong Lyu; Yingjie Liu; Yanyan Gong (Chemical Engineering Journal, 2025)

Temperature shapes the global distribution of organic carbon in lake surface sediments - Yongquan Lin; Sheng Yang; Mengting Zhao; Xuerui Lyu; Lingmei Xu; Wengang Kang; Xinwei Yan; Yurui Zhang; Jianbao Liu (Journal of Geographical Sciences, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

Non-volatile compounds as aroma modulators in Jiangxiang-flavor Baijiu: Regional flavor differentiation and synergistic interactions with volatile aromas - Xiaotong Lyu; Meiyi Zhou; Qian Wang; Lihuan Lang; Kemin Linghu; Chunhui Wei; Liangcai Lin; Paul A. Kilmartin; Cuiying Zhang (Food Chemistry, 2025)

Synergistic integration of redox-active nanoparticles and hierarchical porosity for high-performance osmotic energy harvesting in cellulose-based membranes - Rongrong Zhang; Zhaoyun Lin; Gaojin Lyu; Rui Zhao; Xinrui Wang; Zhen Wang; Chang Geun Yoo (Chemical Engineering Journal, 2025)

Synergistic enhancement of thermoelectric performance in SnTe via Bi and Ge Co-doping - Minwen Yang; Jingyi Lyu; Junyu Lin; Yanqi Huang; Zehao Lin; Rui Zhang; Jing Shuai; Yanglong Hou (Chemical Engineering Journal, 2025)

Distinct responses of fungal and bacterial denitrification genes to seasonal changes, nitrogen deposition and precipitation reduction in subtropical forest soils - Qirun Chen; Fengyi Han; Maokui Lyu; Zhiwei Zeng; Yanjiang Cai; Yuheng Cheng; Zi-Yang He; Milin Deng; Jinsheng Xie; Yongxin Lin (Applied Soil Ecology, 2025)

From colonization to stability: Shifting roles of cyanobacteria and aerobic anoxygenic phototrophic bacteria in coral island biocrust formation and development - Lin Wang; Qingsong Yang; Jing Wen; Lina Lyu; Zhimao Mai; Si Zhang; Jie Li (Applied Soil Ecology, 2025)

PFAS removal from reverse osmosis and nanofiltration brine by granular activated carbon: Thermodynamic insights into salinity effects - Jiefei Cao; Siyuan Feng; Alireza Arhami Dolatabad; Yue Zhi; Baolin Deng; Caihong Liu; Xueyan Lyu; Charlotte S.Q. Christensen; Joseph J. Pignatello; Pan Ni; Shihong Lin; Zongsu Wei; et al. (Water Research, 2025)

The Development of an Automatic Amyloid PET Quantification (AmPQ) Software with MR-based and MR-free Spatial Normalization - Shao-Yi Huang; Kun-Ju Lin; Zong-Jhe Lyu; Ing-Tsung Hsiao (Journal of Medical and Biological Engineering, 2025)

Dose-response pattern of marine macroalgae Gracilariopsis heteroclada to three fluoroquinolones and the cause-effect relationship of dose, growth, toxicity and sorption - Kun Lin; Youyou Guo; Rong Xin; Enyi Xie; Xuefeng Wang; Jianjun Cui; Jinhui Wu; Zhaowei Huang; Yong Liu; Shaoliang Lyu; Sipan Wang; Yongjian Huang; et al. (Algal Research, 2025)

Characterizing regional importance in cities with human mobility motifs in metro networks - Shuyang Shi; Ding Lyu; Lin Wang; Xiaofan Wang; Guanrong Chen (Journal of Transport Geography, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Exploration of ammonia stripping coupled adsorption-membrane filtration process for treating kitchen waste biogas slurry - Shupeng Lin; Tao Lyu; Minmin Pan; Yahan Hou; Chunchun Guo; Zhihao Chen; Renjie Dong; Shan Liu (Environmental Research, 2025)

Hierarchical carbon cloth with Co-N nanoneedle arrays: enabling highly reversible lithium metal anode via enhanced lithiophilicity and structural confinement - Jinping Xu; Meina Huang; Cheng Zhang; Zhen Wang; Xin Xiao; Peiwan Guo; Qianyu Fan; Shize Geng; Xin Lin; Lizhe Liang; Dechao Wang; Taiyu Lyu; et al. (Chemical Engineering Journal, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Estimation of construction and demolition waste and assessment of disposal facility location: An integrated Material Flow Analysis and Geographic Information System approach - Yilin Lyu; Nina Xiong; Yuying Liang; Shuqi Lin; Jia Wang (Resources, Conservation and Recycling, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

3D printing functional materials with extreme regulation of mechanical performances from hydrogel to engineering plastic - Di Liu; Yang Lyu; Zhengwei Lin; Zhongying Ji; Xiaolong Wang; Xinyan Shi (Chemical Engineering Journal, 2025)

Exosome-loaded methacrylated silk fibroin hydrogel delays intervertebral disc degeneration by DKK2-mediated mitochondrial unfolded protein response - Xiao Lu; Zhidi Lin; Liujingzhou Li; Guangyu Xu; Dachuan Li; Zhaoyang Gong; Jiongdong Wu; Tian Gao; Xingyu Guo; Chenpei Xu; Xinlei Xia; Feizhou Lyu; et al. (Chemical Engineering Journal, 2025)

Increased ZNF83 is a potential prognostic biomarker and regulates oxidative stress-induced ferroptosis in clear cell renal cell carcinoma - Zhaojie Lyu; Huming Wang; Fang Dai; Yu Lin; Hantao Wen; Xudong Liu; Xiaotong Feng; Zihan Xu; Lei Huang (Journal of Molecular Medicine, 2025)

The association of apparent temperature with fetal growth: A birth cohort study in Beijing, China - Xin Yuan; Shuang Zhou; Xiaoqing Li; Jinlang Lyu; Lizi Lin; Yuelong Ji; Hui Wang; Jue Liu; Qin Li; Hai-Jun Wang (Sustainable Cities and Society, 2025)

Exploring dialkyl carbonate as a low-carbon fuel for combustion engines: an overview - Guofeng Yang; Qingxuan Wang; Lincheng Li; Delin Lyu; He Lin; Dong Han (Fuel, 2025)

Validation of Automated Standardization Performance for ECDaim Software Developed Using a Taiwan-Specific Database - Yu-Ching Ni; Hui-Chieh Yang; Ing-Tsung Hsiao; Fan-Pin Tseng; Chia-Yu Lin; Wen-Bin Lin; Zong-Jhe Lyu (Journal of Medical and Biological Engineering, 2025)

Co-combustion characteristics of coal gasification fly ash and coal gangue preheated by circulating fluidized bed - Jicheng Hui; Jiangong Lin; Shujun Zhu; Zhaoyang Li; Xiaoyu Zhang; Xiaoyang Cao; Jianguo Zhu; Qinggang Lyu (Waste Management, 2025)

New insights into quercetin's attenuation of TBBPA-induced injury to MCEC cells: Involvement of the p38/NF-κB pathway and pyroptosis - Ke Li; Kun Wang; Tong Xu; Chencong Lyu; Xuejiao Yang; Hongjin Lin; Shiwen Xu (Journal of Environmental Management, 2025)

Harnessing multi-target nanosweepers inhibiting β-amyloid aggregation, scavenging reactive oxygen species and overcoming the blood brain barrier for rescuing Alzheimer’s disease - Yixuan Wang; Chaoren Yan; Yuming Qi; Ruobing Zhao; Yan Wan; Zhaoyuan Lyu; Yansong Li; Zhijuan Wang; Changqing Li; Yuehe Lin; Qian Chen; Shichao Ding; et al. (Chemical Engineering Journal, 2025)

4D printing of continuous carbon fiber reinforced composites with magneto-/electro-induced shape memory effect - Fankuo Jin; Feifan Wang; Peng Guo; Mingfu Lyu; Lihan Wang; Dali Gao; Lin Sang (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Insight into the plasma-catalyst removal process of CH4-NOx under marine LNG engine exhaust conditions: Experiment and chemical kinetics - Chuang Xiang; Lin Lyu; Junjie Liang; Neng Zhu (Process Safety and Environmental Protection, 2025)

Soil CO2 cycle models in karst critical zone: A case study of the soil–cave system - Meifang Wang; Weijun Luo; Yanwei Wang; Guangneng Zeng; Yina Lyu; Jia Chen; Xianli Cai; Lin Zhang; Anyun Cheng; Shijie Wang (CATENA, 2025)

Rapid screening of pottery lipid residue profile via comprehensive two-dimensional gas chromatography - Bin Han; Nanning Lyu; Long Yan; Tao Wang; Jie Gao; Liugen Lin; Huiyun Rao; Yimin Yang (Analytica Chimica Acta, 2025)

Effects of light colors on the growth, body color changes, and phototactic behaviors of green, purple, and white sea cucumbers, Apostichopus japonicus - Haoyu Tong; Xu Wang; Mingxin Lyu; Libin Zhang; Chenggang Lin (Aquaculture, 2025)

Performance and emission characteristics of marine ammonia/diesel dual-fuel engines at different diesel substitution rates - Yongzhong Huang; Lin Lyu; Junjie Liang; He Yang; Neng Zhu; Hao Sang; Xintang Zhang (Fuel, 2025)

A contour integral-based method for nonlinear eigenvalue problems for semi-infinite photonic crystals - Xing-Long Lyu; Tiexiang Li; Wen-Wei Lin (Computer Physics Communications, 2025)

Three-dimensional ordered macroporous nitrogen-doped carbon for efficient adsorption of flavonoids from plant extraction - Chuanmao Li; Wenyuan Lyu; Ruiting Lin; Haoran Liu; Yingfei Wang; Datong Chen; Fengliang Wang; Yingwei Li (Chemical Engineering Journal, 2025)

Enhanced red emission of upconversion nanoparticles via Li+ and Tm3+ codoping and active core-shell construction for sensitive detection of miRNAs - Yingchao Li; Canzhao Tu; Qianshun Chen; Yingying Lin; Baoming Li; Haixia Lyu (Analytica Chimica Acta, 2025)

Polycyclic polyprenylated acylphloroglucinols from the pericarps of Garcinia multiflora champ. ex Benth. with cytotoxic property - Jun Cao; Wen-Yu Lyu; Yujia Zhang; Zhicheng Su; Ting Li; Qingwen Zhang; Lishe Gan; Jin-Jian Lu; Ligen Lin (Phytochemistry, 2024)

A nitrogen-enriched strategy to accelerate the remediation of Cr(VI)-contaminated soil by iron-based materials in microwave fields - Yuxin Liu; Qintie Lin; Jieyi Pan; Yirong Deng; Junli Zheng; Mingchao Lyu; Hao Luo; Yang Luo (Journal of Hazardous Materials, 2024)

Synergetic effects of chlorinated paraffins and microplastics on microbial communities and nitrogen cycling in deep-sea cold seep sediments - Lina Lyu; Yang Wu; Yangjun Chen; Jie Li; Yu Chen; Lin Wang; Zhimao Mai; Si Zhang (Journal of Hazardous Materials, 2024)

Lignocellulose degradation and temperature adaptation mechanisms during composting of mushroom residue and wood chips at low temperature with inoculation of psychrotolerant microbial agent - Xueping Tian; Xiaomeng Qin; Xiaojun Jia; Qingyang Lyu; Siqi Li; Linwei Jiang; Lin Chen; Zhiying Yan; Jun Huang (Environmental Pollution, 2024)

Subjective information in thermal comfort evaluation methods: A critical review - Yuxin Yang; Junmeng Lyu; Zhiwei Lian; Yongxin Xie; Ying Jiang; Junwei Lin; Jianlei Niu (Energy and Buildings, 2024)

Synergistic management of nitrogen contamination in overflow wastewater and algal proliferation in lake receiving wastewater based on electrochemical oxidation process - Ya-Ning Wang; Ding Li; Lin Liu; Jia-Fang Xie; Zhi-Tang Lyu; Quan-Bao Zhao; Yu-Ming Zheng (Process Safety and Environmental Protection, 2024)

Construction of cellulose 3D network composite membrane supported by hydroxylated boron nitride with high surface charge density to achieve high-efficiency osmotic energy harvesting - Rongrong Zhang; Zhen Wang; Rui Zhao; Zhaoyun Lin; Chang Geun Yoo; Guihua Yang; Jiachuan Chen; Gaojin Lyu (Chemical Engineering Journal, 2024)

Temporal characteristics and vertical profiles of atmospheric CH4 at the northern foot of the Qinling Mountains in China - Wanyu Liu; Xue Feng; Zhenchuan Niu; Weijian Zhou; Huilin Chen; Dan Liang; Mengni Lyu; Guowei Wang; Lin Liu (Atmospheric Environment, 2024)

Experimental study on peak shaving during preheating combustion for different coal ranks: Thermal modification and variable load operation - Jicheng Hui; Shujun Zhu; Zhaoyang Li; Jiangong Lin; Xiaoyang Cao; Qinggang Lyu (Fuel, 2024)

Fish Stock Status and Its Clues on Stocking: A Case Study of Acanthopagrus schlegelii from Zhanjiang Coastal Waters, China - Hagai Nsobi Lauden; Xinwen Xu; Shaoliang Lyu; Alma Alfatat; Kun Lin; Shuo Zhang; Ning Chen; Xuefeng Wang (Fishes, 2024)
Global fisheries face overfishing challenges, endangering fish stock and biodiversity. While hatchery release stocking programs aim to bolster fish populations, their effectiveness remains uncertain due to challenges in data acquisition, such as obtaining stocking details and differentiating between wild and stocked individuals. This study evaluates the stock status of black sea bream (Acanthopagrus schlegelii) released in Chinese hatchery programs since the 1980s. Samples from Zhanjiang fish markets (January 2019–October 2021) underwent analysis using the length–weight relationship (LWR), length-based spawning potential ratio (LBSPR), and length-based Bayesian (LBB) methods. The male and female LWRs were W = 0.0188L2.9725 and W = 0.016L3.0284, respectively, and the observed condition factors indicated good health. The estimates imply that the region is conducive to species survival and can sustain its stocking programs. The LBSPR (SPR = 0.21 (0.17–0.25)) and LBB (B/BMSY = 1.1 (0.718–1.34), B/B0 = 0.37 (0.253–0.473)) results suggest a rebuilding population capable of replenishing to more sustainable levels. However, F/M and net selectivity estimates indicate that fishing practices target juvenile fish, limiting the reproductive potential of A. schlegelii. These findings underline the need for enhanced management strategies, including delayed harvesting and the use of size-specific fishing gear, to ensure the long-term sustainability of the species.

Comparative study of atmospheric brown carbon at Shanghai and the East China Sea: Molecular characterization and optical properties - Dongmei Cai; Chunlin Li; Jingxin Lin; Wenwen Sun; Miaomiao Zhang; Tao Wang; Munila Abudumutailifu; Yan Lyu; Xiaojuan Huang; Xiang Li; Jianmin Chen (Science of The Total Environment, 2024)

Ground-based cloud microphysical observations at Mount Lu in the East Asian monsoon region from 2015 to 2020 - Lijun Guo; Jing Duan; Xiaopeng Zhang; Jun Li; Kai Lyu; Yi Chang; Guangxian Lu; Dawei Lin; Tian Luan; Xiaofeng Lou; Baojun Chen (Atmospheric Research, 2024)

Observed surface heat fluxes partitioning during the local growing season over the Tibetan Plateau - Mingshan Deng; Xianhong Meng; Danrui Sheng; Hanlin Niu; Peili Wu; Zhaoguo Li; Lin Zhao; Hao Chen; Lunyu Shang; Shaoying Wang; Shihua Lyu (Agricultural and Forest Meteorology, 2024)

An experimental study on the evolution of flame height and extension length in tunnel fires with arched ceiling confined condition - Xiaochun Zhang; Linjie Chen; Baien Lyu; Hanwei Tang; Xu Peng; Jianye Lin; Zhenyi Zhang; Fei Ren (Tunnelling and Underground Space Technology, 2024)

Clean and efficient process for the recycling of all components from waste printed circuit boards: Pre-treatment, bio-metallurgy, and deep utilization - Chun-chen Nie; Xi-guang Li; Qian-yun Sun; Qiang Gao; Xiang-nan Zhu; Xian-jun Lyu; Lin Li; Xiao-fang You (Journal of Cleaner Production, 2024)

Tough and elastic hydrogel thermocells for heat energy utilization - Xiaolin Lyu; Ziqing Lin; Chunzhi Huang; Xinyue Zhang; Yang Lu; Zhong-Zhen Luo; Piaopiao Zhou; Zhigang Zou (Chemical Engineering Journal, 2024)

Organic carbon negatively affects the diversity of soil nitrous oxide reducers in Chinese fir plantations at a regional scale - Milin Deng; Yong Zheng; Zi-Yang He; Maokui Lyu; Shengsheng Jin; Hao Yang; Hanshuo Zhang; Ji-Zheng He; Yongxin Lin (Applied Soil Ecology, 2024)

An untargeted metabolomics study of cardiac pathology damage in rats caused by low selenium diet alone or in combination with T-2 toxin - Xue Lin; Lichun Qiao; Haobiao Liu; Miaoye Bao; Huan Deng; Lianxu Jia; Xinyue Wen; Feidan Deng; Ping Wan; Yizhen Lyu; Jing Han (Food and Chemical Toxicology, 2024)

Simulation of saturated–unsaturated seepage problems via the virtual element method - Yinghao Sun; Da Li; Lei Jiao; Zhongxin Liu; Yun Yang; Junda Lyu; Shan Lin (Computers and Geotechnics, 2024)

Fungal community composition and function but not diversity were significantly affected by continuous cropping and the interaction with sesame genotype - Fengjuan Lyu; Ruiqing Wang; Rujie Lyu; Hongxin Lin; Zhihua Zhang; Lingen Wei (Rhizosphere, 2024)

Salinity influence on adsorption of lipid molecules in clay minerals: Results from experiments and calculations - Xiao Gao; Zuozhen Han; Gang Zhou; Lin Li; Xiaowei Lyu; Yanyang Zhao; Wenjie Chen; Zhenhua Qi; Fang Liu; Qingqiang Meng; Michael Steiner; Chao Han (Journal of Environmental Chemical Engineering, 2024)

Sophisticated construction of single-atom cobalt catalyst based on microbial hyphae for high-performance hydrogenation - Junhua Kuang; Minghao Gong; Gaofeng Chen; Li Peng; Chen Zou; Zhiqing Peng; Weiming Chen; Yin Li; Yuting Zhang; Tianwei Xue; Chuang Li; Yangyang Dong; et al. (Chemical Engineering Journal, 2024)

On the Shallowing of Antarctic Low-Level Temperature Inversions Projected by CESM-LE under RCP8.5 - Minghu Ding; Lin Zhang; Tingfeng Dou; Yi Huang; Yingyan Luo; Junmei Lyu; Cunde Xiao (Journal of Meteorological Research, 2024)

Hybrid attention network for citrus disease identification - Fukai Zhang; Xiaobo Jin; Gang Lin; Jie Jiang; Mingzhi Wang; Shan An; Junhua Hu; Qiang Lyu (Computers and Electronics in Agriculture, 2024)

Experimental study on reducing BC emissions from a low-speed marine engine by using blended biodiesel and a nitro additive - Ying Sun; Lin Lyu; Miaomiao Wen (Process Safety and Environmental Protection, 2024)

Unraveling the chemosensory characteristics dependence of sauce-flavor baijiu on regionality using descriptive sensory analysis and quantitative targeted flavoromics - Xin Li; Busheng Zhang; Wenxuan Li; Yawen Zhao; Xiaotong Lyu; Xiaolong You; Liangcai Lin; Cuiying Zhang (Food Chemistry, 2024)

MazF-rolling circle amplification combined MALDI-TOF MS for site-specific detection of N6-methyladenosine RNA - Guobin Han; Qiuyuan Lin; Jia Yi; Qian Lyu; Qingwei Ma; Liang Qiao (Analytica Chimica Acta, 2024)

Responses to light in terms of embryonic development and larval phototactic behavior in sea cucumber, Apostichopus japonicus - Haoyu Tong; Xu Wang; Mingxin Lyu; Beini Deng; Libin Zhang; Chenggang Lin (Aquaculture, 2024)

Atmospheric CO2 and 14CO2 observations at the northern foot of the Qinling Mountains in China: Temporal characteristics and source quantification - Wanyu Liu; Zhenchuan Niu; Xue Feng; Weijian Zhou; Dan Liang; Mengni Lyu; Guowei Wang; Xuefeng Lu; Lin Liu; Jocelyn C. Turnbull (Science of The Total Environment, 2024)

Sedimentary characteristics of mixed source fine-grained gravity-flow and its significance for shale oil exploration in a lacustrine depression basin: A case study of the Chang 73 Sub-member of the Triassic Yanchang Formation in Ordos Basin, NW China - Lin Wang; Qiqi Lyu; Linhan Li; Jun Liu; Shunshe Luo; Xuehu Sun; Lei Zhang; Xinshou Xu (Sedimentary Geology, 2024)

Using in situ untargeted flavoromics analysis to unravel the empty cup aroma of Jiangxiang-type Baijiu: A novel strategy for geographical origin traceability - Busheng Zhang; Liangcai Lin; Canjie Zheng; Xuan Liu; Wanjing Cui; Xin Li; Xiaotong Lyu; Cuiying Zhang (Food Chemistry, 2024)

Global multifaceted biodiversity patterns, centers, and conservation needs in angiosperms - Ao Luo; Yaoqi Li; Nawal Shrestha; Xiaoting Xu; Xiangyan Su; Yichao Li; Tong Lyu; Kilara Waris; Zhiyao Tang; Xiaojuan Liu; Luxiang Lin; Yongsheng Chen; et al. (Science China Life Sciences, 2024)

Uptrend of the Western North Pacific Tropical Cyclone Outflow Height during 1959–2021 - Yuan Sun; Zhihao Feng; Wei Zhong; Panmao Zhai; Yanluan Lin; Shuo Lyu (Journal of Meteorological Research, 2024)

Main effects and interactions of multiple key factors related to thermal perception - Yuxin Yang; Junmeng Lyu; Heng Du; Zhiwei Lian; Weiwei Liu; Lin Duanmu; Yongchao Zhai; Bin Cao; Yufeng Zhang; Xiang Zhou; Zhaojun Wang; Xiaojing Zhang; et al. (Science of The Total Environment, 2024)

Unraveling how Fe-Mn modified biochar mitigates sulfamonomethoxine in soil water: The activated biodegradation and hydroxyl radicals formation - Yuying Wang; Haohao Lyu; Yuqian Du; Qilu Cheng; Yuxue Liu; Junwei Ma; Shengmao Yang; Hui Lin (Journal of Hazardous Materials, 2024)

Food search and transport in red imported fire ants (Hymenoptera: Formicidae) under wet conditions - Jintao Lin; Xinya Yang; Hailong Lyu; Xuan Chen; Lei Wang; Cai Wang; Xiujun Wen (Journal of Asia-Pacific Entomology, 2024)

Investigation on the preparation of coal slime flotation microemulsion collector: A combination of experimental and simulation method - Meng He; Jingwei Wang; Jida Niu; Hao Lyu; Liqing Sun; Xiaofang You; Lin Li; Qingbiao Wang (Fuel, 2024)

Effect of reactor operation modes on mitigating antibiotic resistance genes (ARGs) and methane production from hydrothermally-pretreated pig manure - Chunchun Guo; Shupeng Lin; Tao Lyu; Yanfang Ma; Renjie Dong; Shan Liu (Environmental Research, 2024)

Roles and sources of B vitamins in the marine ecosystem - Lin Wang; Hancheng Zhao; Ran Bi; Xiaohan Chen; Zhendong Lyu; Wenhua Liu (Reviews in Fish Biology and Fisheries, 2024)

Eco-friendly approach for enhancing the floatability of non-metallic components in waste printed circuit boards: Adding gutter oil during dry grinding - Chun-chen Nie; Si-qi Jiang; Xi-guang Li; Xiao-ru Wang; Zhi-hao Li; Xiang-nan Zhu; Xian-jun Lyu; Xiao-fang You; Lin Li (Waste Management, 2023)

Ecological benefits of artificial light at night (ALAN): Accelerating the development and metamorphosis of marine shellfish larvae - Mo Zhang; Xiaolong Gao; Qi Luo; Shihui Lin; Mingxin Lyu; Xuan Luo; Caihuan Ke; Weiwei You (Science of The Total Environment, 2023)

Circadian feeding characteristics of different abalone species and construction of a gastrointestinal evacuation model - Mingxin Lyu; Xiaolong Gao; Mo Zhang; Shihui Lin; Caihuan Ke (Aquaculture, 2023)

An accurate and efficient HOS-meshfree CFD coupling method for simulating strong nonlinear wave–body interactions - Chun-Mei Xie; Jun-Cheng Yang; Peng-Nan Sun; Hong-Guan Lyu; Jun Yu; Yong-Lin Ye (Ocean Engineering, 2023)

Differential treatment for time and frequency dimensions in mel-spectrograms: An efficient 3D Spectrogram network for underwater acoustic target classification - Ning Tang; Fei Zhou; Yan Wang; Hao Zhang; Tingting Lyu; Zhen Wang; Lin Chang (Ocean Engineering, 2023)

An operational approach for large-scale mapping of water clarity levels in inland lakes using landsat images based on optical classification - Shijiao Lu; Yingchun Bian; Fangfang Chen; Jie Lin; Heng Lyu; Yunmei Li; Huaiqing Liu; Yang Zhao; Yiling Zheng; Linze Lyu (Environmental Research, 2023)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Examination of the effects of blue light stress on monoamine oxidase-mediated immunomodulatory function in the Pacific abalone, Haliotis discus hannai - Mo Zhang; Xiaolong Gao; Mingxin Lyu; Shihui Lin; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2023)

Improving resilience via capacity allocation and strategic pricing: Co-opetition in a shipping supply chain - Guangmei Lyu; Min Zhao; Qingkai Ji; Xiangmei Lin (Ocean & Coastal Management, 2023)

Fabrication of bimetallic MOF with 2D nanosheets structure and rich active sites for enhanced removal of organic pollutants by activation of peroxymonosulfate - Ning Li; Huanxuan Li; Ran Ji; Sihang Lin; Chen Xu; Jingang Huang; Qingwei Zhou; Shuguang Lyu; Feng Li; Junhong Tang (Journal of Environmental Chemical Engineering, 2023)

Enhanced impact of ENSO-independent Indian Ocean SST on summer precipitation over arid Northwest China - Fuan Xiao; Yushan Lyu; Qiaoyan Wu; Lin Lin; Yudie Li; Huihui He; Jieshan Huang (Global and Planetary Change, 2023)

Synergistic enhanced activation of peroxymonosulfate by heterojunction Co3O4–CuO@CN for removal of oxytetracycline: Performance, mechanism, and stability - Ning Li; Huanxuan Li; Chen Xu; Zhong Zhou; Tao Rao; Ran Ji; Sihang Lin; Jia Du; Shaodan Xu; Shuguang Lyu; Feng Li; Junhong Tang (Environmental Research, 2023)

Rhizosphere bacterial community composition was significantly affected by continuous cropping but not by sesame genotype - Fengjuan Lyu; Wenmeng Zhang; Ruiqing Wang; Rujie Lyu; Hongxin Lin; Zhihua Zhang; Lingen Wei (Rhizosphere, 2023)

Experimental study of deep and flexible load adjustment on pulverized coal combustion preheated by a circulating fluidized bed - Jicheng Hui; Shujun Zhu; Xiaoyu Zhang; Yuhua Liu; Jiangong Lin; Hongliang Ding; Kun Su; Xiaoyang Cao; Qinggang Lyu (Journal of Cleaner Production, 2023)

Understory ferns removal downregulates microbial carbon use efficiency and carbon accrual in previously degraded lands - Cui Deng; Maokui Lyu; Xiaoling Xiong; Josep Peñuelas; Jordi Sardans; Xiaojie Li; Weisheng Lin; Yusheng Yang; Jinsheng Xie (Agricultural and Forest Meteorology, 2023)

Ionospheric disturbance analysis of the January 15, 2022 Tonga eruption based on GPS data - Jiafeng Li; Kejie Chen; Haishan Chai; Jian Lin; Zhiyuan Zhou; Hai Zhu; Mingzhe Lyu (Science China Earth Sciences, 2023)

Developing sustainable and recyclable high-efficiency electromagnetic interference shielding nanocomposite foams from the upcycling of recycled poly(ethylene terephthalate) - Chia-Wei Lee; Chia-Hsing Lin; Lyu-Ying Wang; Yi-Huan Lee (Chemical Engineering Journal, 2023)

Study on the shear-slip process and characteristics of fracture in shale - Chengxing Zhao; Jianfeng Liu; Cheng Lyu; Huining Xu; Hao Lin (Engineering Geology, 2023)

Bifunctional lithiophilic carbon fibers with hierarchical structure for high-energy lithium metal batteries - Taiyu Lyu; Fenqiang Luo; Zhen Wang; Futing Jiang; Shize Geng; Yan Zhuang; Xin Lin; Junkai Chen; Dechao Wang; Lingzheng Bu; Lei Tao; Lizhe Liang; et al. (Chemical Engineering Journal, 2023)

Far-field Coupling and Interactions in Multiple Geospheres After the Tonga Volcano Eruptions - Chieh-Hung Chen; Yang-Yi Sun; Xuemin Zhang; Fei Wang; Kai Lin; Yongxin Gao; Chi-Chia Tang; Jun Lyu; Rong Huang; Qian Huang (Surveys in Geophysics, 2023)

Dataset of Comparative Observations for Land Surface Processes over the Semi-Arid Alpine Grassland against Alpine Lakes in the Source Region of the Yellow River - Xianhong Meng; Shihua Lyu; Zhaoguo Li; Yinhuan Ao; Lijuan Wen; Lunyu Shang; Shaoying Wang; Mingshan Deng; Shaobo Zhang; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2023)
Thousands of lakes on the Tibetan Plateau (TP) play a critical role in the regional water cycle, weather, and climate. In recent years, the areas of TP lakes underwent drastic changes and have become a research hotspot. However, the characteristics of the lake-atmosphere interaction over the high-altitude lakes are still unclear, which inhibits model development and the accurate simulation of lake climate effects. The source region of the Yellow River (SRYR) has the largest outflow lake and freshwater lake on the TP and is one of the most densely distributed lakes on the TP. Since 2011, three observation sites have been set up in the Ngoring Lake basin in the SRYR to monitor the lake-atmosphere interaction and the differences among water-heat exchanges over the land and lake surfaces. This study presents an eight-year (2012–19), half-hourly, observation-based dataset related to lake–atmosphere interactions composed of three sites. The three sites represent the lake surface, the lakeside, and the land. The observations contain the basic meteorological elements, surface radiation, eddy covariance system, soil temperature, and moisture (for land). Information related to the sites and instruments, the continuity and completeness of data, and the differences among the observational results at different sites are described in this study. These data have been used in the previous study to reveal a few energy and water exchange characteristics of TP lakes and to validate and improve the lake and land surface model. The dataset is available at National Cryosphere Desert Data Center and Science Data Bank.

Antifungal activity of ginsenoside CK against Botrytis cinerea by targeting sterol 14α-demethylase cytochrome P450 (CYP51) and the application on cherry tomato preservation - Xiaodi Niu; Xuehui Duan; Siwen Lyu; Lu Liu; Li Lin; Yiding Yu; Hongsu Wang (Postharvest Biology and Technology, 2023)

Carbon-confined Ni based catalyst by auto-reduction for low-temperature dry reforming of methane - Dongyang Shen; Jie Wang; Yue Bai; Shuai Lyu; Yuhua Zhang; Jinlin Li; Lin Li; Guanghui Wang (Fuel, 2023)

A classification-based approach to mapping particulate organic matter (POM) in inland water using OLCI images - Huaiqing Liu; Wenyu Liu; Jie Lin; Heng Lyu; Yunmei Li; Fangfang Chen; Ying Zhao; Jiafeng Xu; Honglei Guo (Environmental Science and Pollution Research, 2023)

Recycling cinder in efficient methane production from wheat straw via solid-state anaerobic digestion (SS-AD) - Hongyi Lyu; Jing Chen; Mengyi Wang; Huaiwen Zhang; Heng Wu; Tairan Liu; Xuanmin Yang; Xiaohui Guo; Xiaojiao Wang; Ping Ai; Zhenyu Li; Minsong Lin; et al. (Chemical Engineering Journal, 2023)

Biodegradation of polylactic acid by a mesophilic bacteria Bacillus safensis - Yujun Wang; Ting Hu; Wanting Zhang; Jinwei Lin; Zhanyong Wang; Shuxia Lyu; Haibin Tong (Chemosphere, 2023)

Bioaccumulation of emerging persistent organic pollutants in the deep-sea cold seep ecosystems: Evidence from chlorinated paraffin - Lina Lyu; Kejing Fang; Zhenchang Zhu; Jie Li; Yu Chen; Lin Wang; Zhimao Mai; Qiqi Li; Si Zhang (Journal of Hazardous Materials, 2023)

Acoustic telemetry system as a novel approach for evaluating the effective attraction of fish to artificial reefs - Shaoliang Lyu; Hagai Nsobi Lauden; Lifei Wang; Guobao Chen; Zhichao Wang; Kun Lin; Xuefeng Wang (Frontiers in Marine Science, 2023)
Due to there being a lack of suitable approaches for evaluating the effectiveness of artificial reefs, two experiments were designed to examine the feasibility of acoustic telemetry, a rapidly developing method for tracking aquatic animals. The first experiment was conducted to understand the deployment procedures of an acoustic telemetry system and determine the appropriate deployment of receivers’ spacing, while the second experiment was conducted to quantify the site fidelity and habitat use of 11 reef fish in the Fangchenggang artificial reef area in the northern South China Sea, China. The results indicated that the logistic regression model was an effective way to balance the detection probability at different distances between the range test transmitter and receiver, with above 50% detection probability within 240 m and 80% detection probability within 110 m. The residency index, as a quantification of site fidelity, was 0.85 ± 0.24. The 100% minimum convex polygon, 95% kernel utilization distribution, and 50% kernel utilization distribution, which are the indicators of habitat use, were 34,522.94 ± 35,548.95, 1,467.52 ± 1,619.05, and 236.01 ± 294.59 m 2 , respectively. High site fidelity and the small spatial scale of habitat use for reef fish demonstrated that artificial reefs were an effective man-made structure to attract fish. Overall, this study supports the feasibility of the acoustic telemetry system, indicating that it provides a good approach for quantifying the associations between artificial reefs and fish.

Soy protein isolate-catechin non-covalent and covalent complexes: Focus on structure, aggregation, stability and in vitro digestion characteristics - Shicheng Dai; Peilong Liao; Yilun Wang; Tian Tian; Xiaohong Tong; Bo Lyu; Lin Cheng; Liming Miao; Weijie Qi; Lianzhou Jiang; Huan Wang (Food Hydrocolloids, 2023)

In vitro and in vivo anti-tumor activity of Antrodia salmonea against twist-overexpressing HNSCC cells: Induction of ROS-mediated autophagic and apoptotic cell death - Hsin-Ling Yang; Yi-An Lin; Sudhir Pandey; Jiunn-Wang Liao; Tzong-Der Way; Yu-lyu Yeh; Siang-Jyun Chen; You-Cheng Hseu (Food and Chemical Toxicology, 2023)

Single-atom Mn anchored on N-doped graphene oxide for efficient adsorption-photocatalytic degradation of sulfanilamide in water: Electronic interaction and mineralization pathway - Honghong Lyu; Pin Li; Jingchun Tang; Weixin Zou; Pengfei Wang; Bin Gao; Lin Dong (Chemical Engineering Journal, 2023)

Study on characteristics of coal gasification fine slag-coal water slurry slurrying, combustion, and ash fusion - Chuandong Ma; Xiaoteng Li; Jianqiao Lyu; Meng He; Zhenhua Wang; Lin Li; Xiaofang You (Fuel, 2023)

Influence and mechanism of alkali-modified sludge on coal water slurry properties - Xiaoteng Li; Chuandong Ma; Jianqiao Lyu; Meng He; Junxiang Wang; Qingbiao Wang; Zhenhua Wang; Xiaofang You; Lin Li (Environmental Science and Pollution Research, 2022)

Feeding strategy trade-off and selection of marine nocturnal gastropods under predation risk - Shihui Lin; Xiaolong Gao; Mo Zhang; Mingxin Lyu; Caihuan Ke (Frontiers in Marine Science, 2022)
The circadian rhythm is one of the most crucial and universal biological rhythms in living organisms. As a typical nocturnal creature, the Pacific abalone ( Haliotis discus hannai ) exhibits rhythmic behaviors in terms of passively selecting whether to avoid predators or to forage, and active adaptation to light cycle changes is regulated by the biological clock. However, no basic data are available to help us to understand these rhythmic behaviors in the abalone species. In the present study, quantification of behavioral data for the abalone and its predator swimming crab Portunus trituberculatus in short-term (24 h) and long-term (40 days) polyculture scenarios suggests that the distance and duration of movement, percentage of feeding individuals, and cumulative duration of feeding of the abalone individuals were significantly lower under the short-term predation risk than the long-term predation risk. The concentrations of 5-hydroxytryptamine (5-HT), cyclic adenosine monophosphate (cAMP), protein kinase A (PKA), and hexokinase (HK) in hemolymph, and expression levels of 5-HT1A receptor and 5-HT2 receptor in cerebral ganglion were significantly higher under the long-term predation risk than the short-term predation risk. The concentration of lactate dehydrogenase (LDH) and glycogen content in adductor muscle of the abalone was significantly higher under the short-term predation risk than the long-term predation risk, thereby implying their role in anaerobic metabolism and aerobic metabolism as primary energy sources under the short-term and long-term predation risk, respectively. The concentrations of 5-HT and cAMP, and the expression levels of Bmal1 and 5-HT2 receptor exhibited no significant signs of cosine rhythmicity under the short-term predation risk, but changes in the movement and feeding behaviors of the abalone still occurred at the night only. Correlation analysis shows that the expression levels of Bmal1 and Clock had significantly positive correlations with the circadian changes in the movement parameters of the abalone, thereby suggesting a dominant role in the rhythmic expression of endogenous circadian clock genes regulating the rhythmic behavior of the abalone. These findings provide new insights into the origin and evolution of biological rhythms in nocturnal marine animals and a reference for developing rational stock enhancement plans, and would improve protection for marine benthic biodiversity.

Functional characterization of piggyBac-like elements from Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) - Jun Lyu; Qin Su; Jinhui Liu; Lin Chen; Jiawei Sun; Wenqing Zhang (Journal of Zhejiang University-SCIENCE B, 2022)

Effect of bio-based surfactant on wettability of low-rank coal surface and its mechanism - Lin Li; Mingpu Liu; Jianqiao Lyu; Xiaoteng Li; Zhihao Li; Mengyu Lin; Chuandong Ma; Meng He; Qingbiao Wang; Hao Yu; Xiaofang You (Environmental Science and Pollution Research, 2022)

Designing and the Pilot Trial of Bivalve Molluscan Fishing Quotas on Maoming Coastal Waters of China, Northern South China Sea - Shaoliang Lyu; Siman Deng; Kun Lin; Jiawei Zeng; Xuefeng Wang (Frontiers in Marine Science, 2022)
In the context of the declining fishery resources, some active management measures have been taken to strive for the sustainable development of fisheries. However, these input-oriented control management measures have not realized the expectation in alleviating the depressing depletion of fishery resources. The fishing quota (FQ) system, an output-oriented control management method, has been proved to be effective in curbing overfishing and conserving fishery resources. However, it has not been formally implemented in China until now. Thus, it is urgent to start the pilot trial on the implementation of the FQ system in China. We firstly formulated a framework for the FQ system on bivalve fisheries and then conducted an empirical analysis based on the field survey of bivalve mollusks in Maoming shallow waters, Guangdong, northern South China Sea. The species composition, dominant species, and density distribution of bivalves were analyzed. The swept-area method was used to assess the total allowable catch (TAC) of bivalves. Each step of the FQ system was discussed in depth. Results showed that a total of 45 bivalve species were identified. Meretrix planisulcata and Ruditapes philippinarum were the two dominant species. The spatial distribution of density varied largely. The estimated TAC value is 4.28 × 10 5 kg which can be allocated to fishermen under the regulations of the FQ system. Finally, the framework for the FQ system was improved in every step of the future procedure, including target species selection, TAC determination, quota allocation, catch report, and fishing supervision. The general framework of the FQ system in this study can also be referenced to other economically important fish or other marine organisms.

Evaluation of surface albedo over the Tibetan Plateau simulated by CMIP5 models using in‐situ measurements and MODIS - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Shaoying Wang; Lunyu Shang; Hao Chen; Shihua Lyu (International Journal of Climatology, 2022)
Surface albedo plays a key role in the energy and water cycles, and reasonable parameterizations of surface albedo will be greatly helpful to improve the simulation of radiation partition in climate models. In‐situ measurements of albedo from five sites over the Tibetan Plateau (TP) and MODIS albedo product are used to evaluate monthly, annual, and seasonal variations of the surface albedo simulated by 24 Global Climate Models (GCMs) archived by the Coupled Model Intercomparison Project Phase 5 (CMIP5). Potential factors contributing to the bias of simulated albedo were investigated. The results show that the monthly albedo of 24 GCMs varied across models, and the difference among the models was smaller in the June–July–August period than the December–January–February period. The ensemble mean albedo of the 24 GCMs was more consistent with the in‐situ measurements than the individual model. The albedo calculated from the BNU‐ESM, GFDL‐CM3, INM‐CM4, MIROC4h, MIROC‐ESM, and MIROC‐ESM‐CHEM models coincided with the observations from June to September, increasing rapidly to above 0.4 from November. However, the annual cycle of surface albedo was insignificant when simulated by some models, such as CanESM2, CSIRO‐Mk3.6.0, CMCC‐CMS, IPSL‐CM5A‐MR, and MPI‐ESM‐MR. Additionally, the surface albedo was overestimated by CMIP5 multi‐model ensemble mean—with a smaller amplitude of daily albedo—compared with the values estimated from in‐situ observations and MCD43A3. In all 24 models, snow albedo parameterization schemes were found to variably fit the attenuation of snow albedo over time. The cold temperature, relatively more precipitation, fresh snow density, and albedo in these models led to large biases in snow depth and ablation. The surface albedo tends to increase without the influence of blowing snow and withered grass on the model's albedo.

Effects of Flow Velocity on the Growth and Survival of Haliotis discus hannai Larvae in the Recirculating Upflow System From the Point of Energy Metabolism - Mo Zhang; Xiaolong Gao; Mingxin Lyu; Shihui Lin; Ying Su; Xuan Luo; Weiwei You; Caihuan Ke (Frontiers in Marine Science, 2021)
For the abalone Haliotis discus hannai , attachment and metamorphosis are crucial stages in the transition from planktonic to benthic life. Increasing the larval metamorphosis rate by artificially controlling the external environment and simulating natural seawater flow is vital to enhance the hatchery efficiency of H. discus hannai . Thus, in the current study, an upflow recirculating aquaculture unit was designed for the rearing of larval abalone, and the larval hatching rate, survival rate, mode of energy metabolism, and expression levels of metamorphosis-related genes at different flow velocities (0, 5, 10, 20, and 40 L/h) were compared and analyzed. At flow velocities less than 20 L/h, no significant differences occurred in larval hatching, survival, and metamorphosis rates, whereas significant differences were recorded at flow rates of 20 and 40 L/h. Differences were also observed in the activity of enzymes, such as hexokinase (HK), pyruvate kinase (PK), lactate dehydrogenase (LDH), succinate dehydrogenase (SDH), and malate dehydrogenase (MDH), as well as glycogen levels, at the higher flow rates. These results suggested that velocity in excess of a certain limit leads to a higher glycolysis rate and transition of energy utilization from aerobic to anaerobic metabolism for the abalone larvae. Compared with conventional still-water aquacultural systems, the flow velocity at 5–10 L/h could maintain the water environment stability, and avoid both fertilized eggs from being densely deposited before hatching and the consumption of energy needed to resist high flow velocities. Thus, these results are useful references to enhance the hatchery efficiency, and to conduct large-scale rearing, of abalone larvae.

Comparative Study of the Feeding Characteristics and Digestion Physiology of Haliotis discus hannai and Haliotis gigantea - Mingxin Lyu; Xiaolong Gao; Mo Zhang; Shihui Lin; Xuan Luo; Weiwei You; Caihuan Ke (Frontiers in Marine Science, 2021)
Abalone ( Haliotis spp.) are typical nocturnal creatures but Haliotis discus hannai is bold and active in the nighttime whereas H. gigantea tends to be timid and inactive. In this study, we quantified and compared differences in movement, feeding, and digestive physiology between H. discus hannai and H. gigantea as well as the potential molecular mechanisms on the basis of video observations and expression levels of genes related to feeding regulation. The feeding behaviors of both species were characterized by significant circadian rhythms ( P < 0.05). However, the distance moved and the cumulative duration of movement were 2.61 and 1.94 times higher, respectively, in H. discus hannai than in H. gigantea over the 24-h cycle. The cumulative duration of feeding by H. discus hannai was only 1.15 times that by H. gigantea , but the feeding time as a percentage of the cumulative duration of movement (FTP) was up to 94.6% for H. gigantea and only 56.0% for H. discus hannai . The peaks for α-amylase activity and NPF expression levels in both species as well as the peak OX 2 R expression level in H. gigantea occurred during 20:00–00:00 h. By contrast, the peaks for alginate lyase activity and NPYR expression levels in H. discus hannai occurred at 16:00 h, when the FTP was significantly higher for H. discus hannai than for H. gigantea . These initial findings quantify specific behavior parameters and thus provide a reference for the selection of appropriate feeding strategies and the proliferation of abalone via bottom sowing.

Growth Differentiation Factor-15 Produces Analgesia by Inhibiting Tetrodotoxin-Resistant Nav1.8 Sodium Channel Activity in Rat Primary Sensory Neurons - Wei Lin; Wen-Wen Zhang; Ning Lyu; Hong Cao; Wen-Dong Xu; Yu-Qiu Zhang (Neuroscience Bulletin, 2021)
Growth differentiation factor 15 (GDF-15) is a member of the transforming growth factor-β superfamily. It is widely distributed in the central and peripheral nervous systems. Whether and how GDF-15 modulates nociceptive signaling remains unclear. Behaviorally, we found that peripheral GDF-15 significantly elevated nociceptive response thresholds to mechanical and thermal stimuli in naïve and arthritic rats. Electrophysiologically, we demonstrated that GDF-15 decreased the excitability of small-diameter dorsal root ganglia (DRG) neurons. Furthermore, GDF-15 concentration-dependently suppressed tetrodotoxin-resistant sodium channel Nav1.8 currents, and shifted the steady-state inactivation curves of Nav1.8 in a hyperpolarizing direction. GDF-15 also reduced window currents and slowed down the recovery rate of Nav1.8 channels, suggesting that GDF-15 accelerated inactivation and slowed recovery of the channel. Immunohistochemistry results showed that activin receptor-like kinase-2 (ALK2) was widely expressed in DRG medium- and small-diameter neurons, and some of them were Nav1.8-positive. Blockade of ALK2 prevented the GDF-15-induced inhibition of Nav1.8 currents and nociceptive behaviors. Inhibition of PKA and ERK, but not PKC, blocked the inhibitory effect of GDF-15 on Nav1.8 currents. These results suggest a functional link between GDF-15 and Nav1.8 in DRG neurons via ALK2 receptors and PKA associated with MEK/ERK, which mediate the peripheral analgesia of GDF-15.

The Significant Role of Radiosonde-measured Cloud-base Height in the Estimation of Cloud Radiative Forcing - Hui Xu; Jianping Guo; Jian Li; Lin Liu; Tianmeng Chen; Xiaoran Guo; Yanmin Lyu; Ding Wang; Yi Han; Qi Chen; Yong Zhang (Advances in Atmospheric Sciences, 2021)

Analysis of stability of the Baihetan arch dam based on the comprehensive method - Wenlong Lyu; Lin Zhang; Baoquan Yang; Yuan Chen (Bulletin of Engineering Geology and the Environment, 2021)

Suitable plant combinations for ecological floating beds in eutrophic subtropical coastal wetlands under different salinities: experimental evidences - J. C. Lyu; G. H. Lin; Z. Y. Fan; W. X. Lin; Z. Dai (International Journal of Environmental Science and Technology, 2020)

Experimental study on dynamic mechanical responses of coal specimens under the combined dynamic-static loading - Pengfei Lyu; Xuehua Chen; Guangbo Chen; Lin Qiu (Arabian Journal of Geosciences, 2020)

CO2 flux of soil respiration in natural recovering karst abandoned farmland in Southwest China - Yanwei Wang; Weijun Luo; Guangneng Zeng; Hanling Yang; Meifang Wang; Yina Lyu; Anyun Cheng; Lin Zhang; Xianli Cai; Jia Chen; Shijie Wang (Acta Geochimica, 2020)

Taurine attenuates isoproterenol-induced H9c2 cardiomyocytes hypertrophy by improving antioxidative ability and inhibiting calpain-1-mediated apoptosis - Weiwei Li; Jiancheng Yang; Qiufeng Lyu; Gaofeng Wu; Shumei Lin; Qunhui Yang; Jianmin Hu (Molecular and Cellular Biochemistry, 2020)

Preparation of Novel ALRCs/nZVI Composite and Its Removal of Cr(VI) from Aqueous - Xuan Zhang; Xiao-qiang Cao; Guang Li; Jijie Yin; Di Zhang; Mingzhen Li; Na Meng; Liang Dong; Xian-jun Lyu; Lin Li; Jun Qiu; Yan Zhang; et al. (International Journal of Environmental Research, 2020)

Correction to: Microsatellite records for volume 10, issue 2 - Dan Yu; Xueyun Ding; Zhi Zhang; Yu Zeng; Huanzhang Liu; Lin Wang; Ye Gong; Xingtu Liu; Xianguo Lyu; Gregory R. McCracken; Francisca V. Valenzuela-Aguayo; Evelyn M. Habit; et al. (Conservation Genetics Resources, 2020)

Correction to: Effects of nitrogen addition on DOM-induced soil priming effects in a subtropical plantation forest and a natural forest - Yuexin Fan; Xiaojian Zhong; Teng-Chiu Lin; Maokui Lyu; Minhuang Wang; Weifang Hu; Zhijie Yang; Guangshui Chen; Jianfen Guo; Yusheng Yang (Biology and Fertility of Soils, 2020)

Effects of nitrogen addition on DOM-induced soil priming effects in a subtropical plantation forest and a natural forest - Yuexin Fan; Xiaojian Zhong; Teng-Chiu Lin; Maokui Lyu; Minhuang Wang; Weifang Hu; Zhijie Yang; Guangshui Chen; Jianfen Guo; Yusheng Yang (Biology and Fertility of Soils, 2020)

Gastrodin ameliorates microvascular reperfusion injury–induced pyroptosis by regulating the NLRP3/caspase-1 pathway - Wenjing Sun; Hongquan Lu; Lechun Lyu; Ping Yang; Zhi Lin; Ling Li; Lin Sun; Di Lu (Journal of Physiology and Biochemistry, 2019)

Identification and expression profiling of selected MADS-box family genes in Dendrobium officinale - Yue Chen; Qi Shen; Ping Lyu; Renan Lin; Chongbo Sun (Genetica, 2019)

Effect of roughness lengths on surface energy and the planetary boundary layer height over high-altitude Ngoring Lake - Zhaoguo Li; Shihua Lyu; Lijuan Wen; Lin Zhao; Xianhong Meng; Yinhuan Ao (Theoretical and Applied Climatology, 2018)

Recombinant rabies virus expressing interleukin-6 enhances the immune response in mouse brain - Jun Luo; Boyue Zhang; Yuting Wu; Qin Tian; Meijun Mo; Teng Long; Mingzhu Mei; Ruqi Fan; Ziyu Lyu; He Jiang; Fan Wu; Yingyi Lin; et al. (Archives of Virology, 2018)

Land use change exerts a strong impact on deep soil C stabilization in subtropical forests - Maokui Lyu; Jinsheng Xie; Liisa Ukonmaanaho; Miaohua Jiang; Yiqing Li; Yuehmin Chen; Zhijie Yang; Yanxiang Zhou; Weisheng Lin; Yusheng Yang (Journal of Soils and Sediments, 2017)

Punicalagin protects bovine endometrial epithelial cells against lipopolysaccharide-induced inflammatory injury - An Lyu; Jia-jia Chen; Hui-chuan Wang; Xiao-hong Yu; Zhi-cong Zhang; Ping Gong; Lin-shu Jiang; Feng-hua Liu (Journal of Zhejiang University-SCIENCE B, 2017)

Improved allometric equations for estimating biomass of the three Castanopsis carlesii H. forest types in subtropical China - Kaimiao Lin; Maokui Lyu; Miaohua Jiang; Yuehmin Chen; Yiqing Li; Guangshui Chen; Jinsheng Xie; Yusheng Yang (New Forests, 2017)

A genome-wide analysis of the ASYMMETRIC LEAVES2/LATERAL ORGAN BOUNDARIES (AS2/LOB) gene family in barley (Hordeum vulgare L.) - Bao-jian Guo; Jun Wang; Shen Lin; Zheng Tian; Kai Zhou; Hai-ye Luan; Chao Lyu; Xin-zhong Zhang; Ru-gen Xu (Journal of Zhejiang University-SCIENCE B, 2016)

Magnolol pretreatment attenuates heat stress-induced IEC-6 cell injury - Chen Mei; Sha-sha He; Peng Yin; Lei Xu; Ya-ran Shi; Xiao-hong Yu; An Lyu; Feng-hua Liu; Lin-shu Jiang (Journal of Zhejiang University-SCIENCE B, 2016)

Turbulent transfer coefficient and roughness length in a high-altitude lake, Tibetan Plateau - Zhaoguo Li; Shihua Lyu; Lin Zhao; Lijuan Wen; Yinhuan Ao; Shaoying Wang (Theoretical and Applied Climatology, 2016)

Impact of meteorological drought on streamflow drought in Jinghe River Basin of China - Lin Zhao; Aifeng Lyu; Jianjun Wu; Michael Hayes; Zhenghong Tang; Bin He; Jinghui Liu; Ming Liu (Chinese Geographical Science, 2014)

Effects of crude oil contamination on soil physical and chemical properties in Momoge wetland of China - Ying Wang; Jiang Feng; Qianxin Lin; Xianguo Lyu; Xiaoyu Wang; Guoping Wang (Chinese Geographical Science, 2013)

An Informetric Profile of Water Resources Management Literatures - Jun-Lin Ren; Peng-Hui Lyu; Xin-Mu Wu; Fei-Cheng Ma; Zhi-Zhang Wang; Gang Yang (Water Resources Management, 2013)

Mitochondrial proteomics analysis of tumorigenic and metastatic breast cancer markers - Yi-Wen Chen; Hsiu-Chuan Chou; Ping-Chiang Lyu; Hsien-Sheng Yin; Fang-Liang Huang; Wun-Shaing Wayne Chang; Chiao-Yuan Fan; I-Fan Tu; Tzu-Chia Lai; Szu-Ting Lin; Ying-Chieh Lu; Chieh-Lin Wu; et al. (Functional & Integrative Genomics, 2011)

Erratum to: Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)

Role of the Conserved Thr399 and Thr417 Residues of Bacillus licheniformis γ-Glutamyltranspeptidase as Evaluated by Mutational Analysis - Rui-Cin Lyu; Hui-Yu Hu; Lih-Ying Kuo; Huei-Fen Lo; Ping-Lin Ong; Hui-Ping Chang; Long-Liu Lin (Current Microbiology, 2009)